Analysis of Work Time Effectiveness in Light Gauge Steel Roof Frame Work - Desi Yasri; Rahmat Saputra; Neri Puspita Sari (Teknik Sipil Universitas Riau, 2026)
Construction labor productivity continues to be a global challenge, particularly in Indonesia, due to skilled labor shortages and resultant inefficiencies like idleness. Despite prior research on various construction tasks, a gap exists in understanding labor efficiency in modern light-gauge steel frame roof construction, which necessitates distinct work patterns. This study empirically investigates labor efficiency in light-gauge steel roof framing within a housing complex in Pekanbaru using the Work Sampling technique to ascertain the Labor Utilization Rate (LUR) and identify influencing factors. Findings indicate that design complexity significantly affects LUR, with Gable roofs (87.17%) demonstrating higher efficiency than Pyramid Hip roofs (84.36%). Team size and effective coordination are crucial, as Team C (three workers) achieved optimal output. Although essential contributory activities correlate positively with effective work, idle time, often due to fatigue or waiting, remains a challenge, particularly in complex tasks. This research provides critical insights and practical measures to enhance productivity in contemporary light-gauge steel roof construction.